TEACHER PERFORMANCE REVIEWED FROM LEADERSHIP, DISCIPLINE, MOTIVATION AND ORGANIZATIONAL CULTURE (Study at SMP Batik Surakarta) - Eni Nuryati; Bambang Mursito; Ida Aryati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The research aims at finding out the influence of the following variables; leadership, discipline, motivation, and organizational culture toward teacher performance in SMP Batik Surakarta both simultaneously and partially. The researcher employs descriptive quantitative research. The population is 45 teachers in SMP Batik Surakarta. The researcher also employs the census technique for sampling technique which consists of 45 respondents. Data collecting technique is using questionnaire while data analyzing technique is using statistical analysis with multiple linear regression test. The finding of the research shows that leadership, discipline, motivation, and organizational culture contribute significant influence toward teacher affected by other variables such as competence, work environment, and others. Keywords: Teacher performance, leadership, discipline, motivation, and organizational culture.